1973
DOI: 10.1104/pp.51.2.289
|View full text |Cite
|
Sign up to set email alerts
|

Multiphasic Absorption of Glucose and 3-O-Methyl Glucose by Aged Potato Slices

Abstract: The isotherm for glucose absorption by aged potato (Solanum tuberosum var. Russet Burbank) discs shows four distinct phases in the concentration ranges 1.0 to 75 /AM, 75 gM to 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
3

Year Published

1974
1974
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 20 publications
1
25
3
Order By: Relevance
“…However, system II data in the present study are not consistent with a number of reports of a nonsaturating second phase (2,16,30). These studies stand in contrast to the work of Linask and Laties (20), who found multiple saturations of uptake. A nonsaturating second phase could reflect diffusional uptake induced by high external sugar concentrations, a possibility ruled out here by the high sucrose concentration (approximately 0.8 M) observed in the minor vein phloem (11 (27) are well within the range of system 1 rates.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, system II data in the present study are not consistent with a number of reports of a nonsaturating second phase (2,16,30). These studies stand in contrast to the work of Linask and Laties (20), who found multiple saturations of uptake. A nonsaturating second phase could reflect diffusional uptake induced by high external sugar concentrations, a possibility ruled out here by the high sucrose concentration (approximately 0.8 M) observed in the minor vein phloem (11 (27) are well within the range of system 1 rates.…”
Section: Discussioncontrasting
confidence: 99%
“…This conclusion is based on solute distributions in sugar beet leaves (11), as well as on the feasibility of the other possible distributions (14,21). The changes postulated in a single carrier enzyme to produce a biphasicuptake curve may involve isozymelike differences in the carrier enzyme, induced by the external substrate concentration (19,20,23 (20) for 3-0-methyl glucose uptake by potato slices. However, system II data in the present study are not consistent with a number of reports of a nonsaturating second phase (2,16,30).…”
Section: Discussionmentioning
confidence: 99%
“…Multiphasic responses relating the rate of uptake to the concentration are familiar in ion uptake studies (18) and have also been shown for sugar uptake as a function of the external sugar solution in castor bean seedlings (19), tobacco cells (3), and in sugar beet leaves (27). These similar relationships may suggest common mechanisms but the cause of the multiphasic responses has yet to be established.…”
Section: General Features Of Carbon 1 1 Translocationmentioning
confidence: 75%
“…Uptake of 2-deG by maize seedling roots exhibited Michaelis-Menten kinetics in each of the two concentration ranges tested, 0.05 to 1 mm and 3 to 40 mm. Hexose uptake by potato slices exhibits a similar behavior, with four phases detected (9), and multiphasic absorption of amino acids has also been reported (5). Ophn A concentrations as low as 2 ,ug/ml (5 ,UM) inhibited 2-deG uptake significantly (Fig.…”
Section: Resultsmentioning
confidence: 62%